Sociolinguistic tensions and educational implications of gender-inclusive language - Gallardo-Hurtado, Miguel (2026)
Through language, individuals construct the symbolic universe of meanings that shapes their identity, with gender being a category that encompasses the discursive practices expressing the social representation of the masculine-feminine binary. However, certain identities remain politically invisibilized through the use of androcentric terms, a practice that hetero-designates and leaves unnamed a diversity of sex-gendered feelings and expressions. In response, inclusive language emerges as a proposal aimed at rendering visible subjective positionings beyond the hegemony of the "generic masculine." With the aim of approaching this phenomenon from a novel perspective compared to previous literature—which is predominantly focused on the morphological controversy—the original contribution of this article lies in analyzing the pedagogical and sociolinguistic tensions generated by its coexistence alongside the standardized norm. To this end, a critical review of relevant literature from the fields of sociolinguistics, gender studies, and education is conducted. Two perspectives are proposed to understand the functions and uses of inclusive language: one focused on factors external to the language—social movements, political and economic ideologies, and cultural transformations—and another on internal elements—the linguistic system and its rules. Subsequently, the morphological change in Spanish resulting from the inclusion of the letter "e" is analyzed, along with its effects in institutional, educational, and social spheres. Finally, it is concluded that inclusive language constitutes an ethical-political stance for identity visibilization, although it remains insufficient in the face of a clearly sexist and patriarchal social system.